The Effectiveness of Underwater LED as a Fish Aggregating Device on a Fixed-Liftnet in Pangkep Waters - U, Fatma; Kurnia, Muhammad; Musbir, Musbir; Sahil, M. Sahil Rizky Bin; Putera, Dion Pratama; Al Haq, Suci Insyirah (Torani Journal of Fisheries and Marine Science, 2022)
The rapid development of electrical technology in the field of fishing, especially utilizing the light to collect fish into the catchable area. Generally, Light emitting diode (LED) lamps for fishing are placed above the water surface. The success of this technology has become the basis for conducting experiments with the position of the lamp in the water to see its effectiveness as a fish collection device. The aim is to develop the application of light fishing technology by; (1) testing the effectiveness of using LED lights in collecting fish in the fixed lift-net catchable area to increase the number of catches; (2) assessing the quality of the catch, namely main and by-catch. The research was carried out in May-October 2022 in the Pangkajene and Islands Regency waters. The case method is one unit of fixed lift-net using 4 units of LED underwater lights with a power of 60 W. Data collecting with experimental fishing, namely following fishing operations for 40 trips. The parameters analyzed were the number and types of catches and the effectiveness of fishing gear based on fishing trips. The results showed that the catches types obtained were 15 species with 101.72 kg total catch. The number of catches is not significant, but the results of this study provide one hope, especially for Mitra fishermen. The innovation of LED underwater lights is new information that has good prospects as a more effective and environmentally friendly light capture device. Kata kunci: Lampu Celup LED, bagan tancap, Perairan Pangkep